Pengembangan modul pembelajaran etno-project geometri analitik - Senjayawati, Eka; Anita, Ika Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research aims to develop an analytical geometry ethno-project module. This research was conducted at IKIP Siliwangi, with 50 students as research subjects. This research uses Research and Development (R & D) ADDIE module. This research concludes. Based on the results of the development research that has been carried out, it can be concluded that the development of the analytical geometry ethno-project module has obtained very valid, practical and very effective qualities, so that the learning module is suitable for use in further analytical geometry learning. Apart from that, from the results of the development of this learning module, students can increase their creativity in the form of skills in making analytical geometric batik designs in the form of drawings in analytical geometry including: triangles, quadrilaterals, circles, parabolas, ellipses and hyperbolas.